qanda-logo
apple logogoogle play logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Calculate the differentiation
Answer
circle-check-icon
expand-arrow-icon
Graph
$y = 2 x - 3$
$x$Intercept
$\left ( \dfrac { 3 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 3 \right )$
$y = 2x-3$
$x = \dfrac { 1 } { 2 } y + \dfrac { 3 } { 2 }$
$ $ Solve a solution to $ x$
$y = \color{#FF6800}{ 2 } \color{#FF6800}{ x } - 3$
$ $ Move $ x $ term to the left side and change the sign $ $
$y \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = - 3$
$\color{#FF6800}{ y } - 2 x = - 3$
$ $ Move the rest of the expression except $ x $ term to the right side and replace the sign $ $
$- 2 x = - 3 \color{#FF6800}{ - } \color{#FF6800}{ y }$
$- 2 x = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ y }$
$ $ Organize the expression $ $
$- 2 x = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$ $ Change the sign of both sides of the equation $ $
$2 x = y + 3$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
$ $ Divide both sides by the same number $ $
$\color{#FF6800}{ x } = \left ( \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
$x = \left ( y + 3 \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
$ $ Convert division to multiplication $ $
$x = \left ( y + 3 \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$x = \left ( \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$ $ Multiply each term in parentheses by $ \dfrac { 1 } { 2 }$
$x = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$x = \dfrac { 1 } { 2 } y + \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$ $ Calculate the product of rational numbers $ $
$x = \dfrac { 1 } { 2 } y + \color{#FF6800}{ \dfrac { 3 } { 2 } }$
$\dfrac {d } {d x } {\left( y \right)} = 2$
Calculate the differentiation of the logarithmic function
$\dfrac {d } {d \color{#FF6800}{ x } } {\left( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right)}$
$ $ Calculate the differentiation $ $
$\color{#FF6800}{ 2 }$
$ $ 그래프 보기 $ $
Linear function
Solution search results
search-thumbnail-System of Linear $m$ $=o\pi $ $m$ $b$ $=0\pi $ $b_{2}$ Graph Kinds of 
Equation Graph 
$1.$ $y=2x+2$ 
$2y=4x+4$ 
$2$ $y=x.5$ 
$y=-x+3$ 
$3$ $y=2x-3$ 
$y=2x+4$
7th-9th grade
Algebra
search-thumbnail-$=$ 
$x+3y=$ $2x-3$ $y$ $-3$ $=12$
10th-13th grade
Other
search-thumbnail-Substitution Method 
$θ$ $2$ $-x+=-1$ 
$x-3y=-3$ $\dfrac {\dfrac {-3y=-\left(nx-} {-3-3}^{3}} {y=2x-3}$ $-x+\left(2x-3\right)=1$ 
$-x+2x-3=-1$ 
$x-3=$ 
$=-1-3$ 
$\dfrac {x=-1} {x=-4}$ 
$3$ 
$y=2x-3$ $=2\left(-4\right)-3$ $x=-4$ 
$-8-3$ 
$-1$
7th-9th grade
Other
search-thumbnail-$2$ $y=2x-3$ 
$y=x+5$ 
$\left(8,13\right)$
7th-9th grade
Other
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo